Pengaruh Orientasi Kewirausahaan dan Inovasi terhadap Kinerja Usaha Pada Home Industri Kerupuk di Desa Kedungrejo Sidoarjo - Arin Indawati; Harti Harti (Ekonomis: Journal of Economics and Business, 2022)
One of the industrial center of Kerupuk is in Sidoarjo, which is located in the Jabon sub-subdistrict. This industrial center of Kerupuk is known as “Kampung Kerupuk”, which each of the houses in the sub-district produces Kerupuk. This study aims to examine the effect of entrepreneurial orientation on business performance, the effect of innovation on business performance, and effect of entrepreneurial orientation and innovation on business performance of home industry of kampong kerupuk in Kedungrejo, Sidoarjo.  The type of research is quantitative with a sample of 31 participants with the saturated sample method.  The data collection technique uses questionnaires by giving personal questions to the participants.  The analysis technique uses multiple linier regression. The results show that entrepreneurial orientation has no positive effect and significant on business performance, innovation has a positive and significant effect on business performance.  Entrepreneurial orientation and innovation have a positive and significant impact on business performance on business performance of home industry of Kampung Kerupuk in Kedungrejo Sidoarjo.